Pengaruh Edukasi PHBS Terhadap Tingkat Pengetahuan Remaja Putri Sebagai Upaya Pencegahan Stunting di SMP ITech Pasim Ar-Rayyan - Filda Nurfadilah; Dhinny Novryanthi; Asep Suryadin (Lembaga Pengembangan Kinerja Dosen, 2026)
Stunting remains a major public health problem caused by chronic malnutrition and poor sanitation practices, particularly in developing countries. Adolescents, especially girls, play a crucial role in stunting prevention as future mothers, yet their knowledge related to clean and healthy living behaviors is often limited. This study aimed to analyze the effect of Clean and Healthy Living Behavior (PHBS) education on the knowledge level of adolescent girls as an effort to prevent stunting. A quantitative pre-experimental study with a one-group pretest–posttest design was conducted among 68 female students at SMP ITech Pasim Ar-Rayyan using total sampling. Data were collected through structured pretest and posttest questionnaires, followed by PHBS education delivered through lectures and discussions. Data analysis included univariate analysis and bivariate analysis using the Wilcoxon test. The results showed a substantial increase in the mean knowledge score from 65.22 before the intervention to 98.09 after the intervention, with a statistically significant difference (p < 0.001). These findings indicate that PHBS education significantly improves adolescents’ knowledge regarding stunting prevention. This study implies that structured health education programs in junior high schools are effective strategies to strengthen early stunting prevention efforts and promote long-term healthy behaviors among adolescent girls